2007
DOI: 10.1245/s10434-007-9470-0
|View full text |Cite
|
Sign up to set email alerts
|

Breast Papillomas in the Era of Percutaneous Needle Biopsy

Abstract: Benign breast papillomas diagnosed by CNB have a low risk of malignancy and do not need excision. However, they should be considered high risk lesions which require serial radiographic monitoring. Papillomas associated with atypia or malignancy should continue to be excised.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
2
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(55 citation statements)
references
References 26 publications
2
48
2
3
Order By: Relevance
“…On the other hand, other researchers have supported selective excision in cases of atypia or in the presence of risk factors. [2][3][4]9,[13][14][15][16]18,[29][30][31][32][33] Table 4 shows the published data on papillomas confirmed by core needle biopsy and subsequent surgical excision and their upgrade rates to malignancy. These studies reported their rates of upgrade from benignity on core needle biopsy to malignancy and papilloma with atypia after surgical excision.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, other researchers have supported selective excision in cases of atypia or in the presence of risk factors. [2][3][4]9,[13][14][15][16]18,[29][30][31][32][33] Table 4 shows the published data on papillomas confirmed by core needle biopsy and subsequent surgical excision and their upgrade rates to malignancy. These studies reported their rates of upgrade from benignity on core needle biopsy to malignancy and papilloma with atypia after surgical excision.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, prior studies have shown that papillomas with atypia diagnosed at core needle biopsy were more often upgraded histologically to malignancy than benign papillomas after surgical excision. [2][3][4][5][6][10][11][12][13]25,33,34,38 Some studies reported atypical papilloma as a generalized risk factor for the development of breast cancer. [39][40][41] Therefore, surgical excision has been recommended as a management strategy for atypical papillomas at core needle biopsy.…”
Section: Sohn and Park-sonographically Guided Core Needle Biopsy And mentioning
confidence: 99%
See 1 more Smart Citation
“…The published literature reports upgrade rates to carcinoma following a diagnosis of benign papilloma at CNB ranging from 0% to 29% [1][2][3]. Some authors believe that benign papillomas diagnosed at CNB with imaging concordance may be safely managed with clinical and imaging follow-up [6,7,[12][13][14][15][16][17][18][19][20]. Others advocate surgical excision to exclude any associated malignancy [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Reported upgrading rates from benign papillary lesions diagnosed by CNB to malignant papillary lesions diagnosed on subsequent surgical excision range from 0% to 29% (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15). Some investigators have suggested that benign papillary lesions without atypia diagnosed by CNB, in combination with concordant imaging findings, can be safely followed without further surgery (2-7).…”
mentioning
confidence: 99%